The generalized Bergshoeff-de Roo identification.: Part II - Baron, Walter Helmut (2021)
We recently introduced a T-duality covariant mechanism to compute all-order higher- derivative interactions in the heterotic string. Here we extend the formalism to account for a two-parameter family of corrections that also include the bosonic string and HSZ theory. We use our result to compute the full second order Double Field Theory (DFT) for generic values of the parameters, including the generalized Green-Schwarz transformation and its invariant action.